Penguatan Konsep Dasar Fisika Dengan Metode Pembelajaran Gasing Pada Siswa dan Guru MA Pondok Pesantren Aikmual Lombok Tengah NTB - Hiden - Hiden; Lily Maysari Angraini; Marzuki Marzuki; Susi Rahayu (Universitas Mataram, 2020)
For a long period, some students in schools thought that Physics and Mathematics were difficult subjects. These two subjects are a scourge for students in most schools, not only in the NTB area but also in various other regions throughout Indonesia. For this reason, multiple efforts need to be made to overcome these learning difficulties. Learning Physics and Mathematics should emphasize providing direct experience to develop student competencies, directed to